Effects of probiotic and stocking density on nile tilapia fingerlings (oreochromis niloticus) productive performance. - Prado Rebolledo, Omar Francisco; García Márquez, Luis Jorge; Macedo Barragán, Rafael Julio; García Curiel, José Luis; Sánchez Barajas, Maximiliano; Téllez Isaías, Guillermo (Revista Científica de la Facultad de Ciencias Veterinarias, 2014)
Â A study was conducted with the purpose to assess the effect of a commercial probiotic and stocking density on productive performance of Nile tilapia (Orechromis niloticus) fingerlings. Fin gerlings were stocked in four 16.56-m3 aerated concrete tanks at two initial densities, low (50 fish/m3) and high (100 fish/m3) and fed four times a day with a commercial food sprayed with 2.6 or 6.6 g/kg food of a commercial probiotic containing strains of Lactobacillus acidophilus and Pediococcus acidilacticii, and inactivated Saccharomyces cerevisiae. Water temperature ranged between 25.9 to 26.1 °C, dissolved oxygen level was 4.95 mg/L and pH value was about 6.9. Daily weight gain, final weight and body length, height and width were greater (P<0.05) in fish reared at low density and added with 2.6 g/kg of probiotic. Specific growth rate was greater (P<0.05) in fish reared at low density without probiotic and in fish reared at high density and fed 6.6 g/kg of probiotic. Inclusion of probiotic improved (P<0.05) feed conversion regardless of stocking density but the cost of feed was significantly increased (P<0.05) by the addition of 6.6 g/kg of probiotic. It can be conclude that the addition of 2.6 g/kg of probiotic improved productive performance of tilapia fingerlings and juveniles rearing at low densities without a significantly increasing the cost of feeding. Productive performance of fish reared at high stocking density could be successfully improved with the addition of 6.6 g/kg of probiotic.